The Effect of Training Methods and Agility on Reaction Speed Of Por and PKO FIKKM UNIMA Students - Richmond Piet Armando Pandey; Agustinus R. J. Sengkey; Eduard E. Kumenap (International Journal of Public Health, 2024)
This research is an experimental research withThe research design used in this study is "Treatment by blocks design 2 x 2", or treatment of a 2 x 2 factorial experimental research design. The population in this study was 66 students from the POR and PKO FIKKM UNIMA departments. The sample was 40 students based on calculations using the Slovin formula, while the sampling technique used was Simple Random Sampling. Data collection for the agility test on March 25, 2024 and continued with the Results Test on May 7, 2024. Where the treatment was given 16 times, with a frequency of 3 times a week. The data analysis technique used was ANOVA with a significance level of 5%. The results of the study showed that: 1). There is a significant difference in the effect between SSD training and SRBD training on reaction speedon POR and PKO FIKKM UNIMA students, where Fo = 5.69 is greater than Ft = 4.11;. 2.) There is a difference in the influence of SSD and SRBD training methods on POR and PKO FIKKM UNIMA students who have high agility, where Qh = 5.97 is greater than Qt = 3.79.;3.) There is no difference in the influence of SSD and SRBD training methods on POR and PKO FIKKM UNIMA students who have low agility, where Qh = 1.56 is smaller than Qt = 3.79.;4.) Interaction between SSD and SRBD training methods of agility training types (high and low) on the reaction speed of POR and PKO FIKKM UNIMA students, whereobtained an average score of the SSD training method group that has high agility of 51.15 and an average score of the SSD training method group that has low agility of 42.9. With an average score of the SRBD training method group that has high agility of 44.85, and an average score of the SRBD training method group that has low agility of 44.55.